Estudio clínico y epidemiológico de un brote de bronquiolitis. - Machado Esparza, L.; Peralta Rodríguez, J.; Camejo Acosta, P.; Velazco Collantes, F.; Felipe Ávila, E.; Hernández Najarro, R.; Iglesias Vallés, A.; Bolufer, B. (Revista Cubana de Pediatría, 2023)
Estudio de 764 casos ingresados.